Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species - Selis, Marco (Zootaxa, 2017)
The Zethus luzonensis Giordani Soika, 1941, species-group is revised. A new species from Mindanao and Luzon in the Philippine Islands, Zethus soikai sp. nov., is described and illustrated. The female of Zethus luzonensis is redescribed and the true male is described. A key to the species of the group is provided.